2017
DOI: 10.1152/ajpcell.00158.2016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low-density lipoprotein-induced microparticles promote endothelial monocyte adhesion via intercellular adhesion molecule 1

Abstract: Oxidized low-density lipoprotein (oxLDL) accumulates early in atherosclerotic lesions and plays an important role in the progressive formation of atherosclerotic plaques. Endothelial derived microparticles (EMPs) form a heterogeneous population of <1-μm particles that shed from endothelial membranes upon activation. While EMPs are shown to be involved in atherosclerotic pathophysiology and progression, there is no report regarding the relationship between oxLDL and EMPs. In this study, we aim to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…In either case, the effects of OxLDL on the release of MVs by platelets in vivo remain to be elucidated. Stimulation of ECs with OxLDL has also been found to trigger the release of MVs, which, in turn, induce the expression of ICAM-1 and promote monocyte adhesion to ECs [82]. However, a direct procoagulatory role for OxLDL-induced ECderived MVs still needs to be established.…”
Section: Mvs and Oxidized Lipoproteinsmentioning
confidence: 99%
“…In either case, the effects of OxLDL on the release of MVs by platelets in vivo remain to be elucidated. Stimulation of ECs with OxLDL has also been found to trigger the release of MVs, which, in turn, induce the expression of ICAM-1 and promote monocyte adhesion to ECs [82]. However, a direct procoagulatory role for OxLDL-induced ECderived MVs still needs to be established.…”
Section: Mvs and Oxidized Lipoproteinsmentioning
confidence: 99%
“…1 and summarized in Table 1. Indeed, stimulation of EC with oxidised LDL (ox-LDL) particles can trigger the release of intercellular CAM (ICAM)-1-rich EV that can be transferred to other EC promoting monocyte adhesion [36]. Furthermore, a number of studies have reported that pro-inflammatory molecules can stimulate the release of leukocyte-derived EV that target EC and promote the recruitment of other leukocytes, feedback looping this process [37][38][39][40][41].…”
Section: Leukocyte Recruitmentmentioning
confidence: 99%
“…It has been shown that oxLDL, in a time-and dose-dependent manner, promotes the in vitro release of endothelial MV rich in intercellular adhesion molecule 1 (ICAM-1) [63], which can be transferred from MV to endothelial cells increasing monocyte adhesion to endothelial cells [64], further propagating the atheroprone effects of oxLDL even in its absence. Moreover, enrichment of THP-1 monocytic cells with unsterilized cholesterol resulted in increased MV production [65], and these MV induced extensive leukocyte rolling and adherence to the endothelium.…”
Section: Crosstalk Between Lipoproteins and MVmentioning
confidence: 99%